PREVALENCE OF ANEMIA ASSOCIATED WITH MENSTRUAL DISORDERS AMONG NURSING STUDENTS IN A PRIVATE NURSING COLLEGE AT KARACHI - CHANNAR, HB; SAMO, AA; CHAPSI, A; CHANDO, K; HAQ , MU; MAHAR, S (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate the prevalence of anemia among nursing students at a private college in Karachi and its association with menstrual problems. The institution approved the study and conducted it with the participation of 144 nursing students who provided informed consent. A pretested questionnaire was used to collect data to estimate the risk factors for anemia in nursing students, and hematological examinations were conducted on their blood samples at Jinnah Sindh Medical University Hospital. The data was analyzed using SPSS version 20.0. The results showed that 52.7% of nursing students suffered from anemia. Interviews with the students revealed that 70.1% had a monthly menstrual flow of 5-7 days, 9.5% had a flow of 3-5 days, and 22.9% had a flow of less than three days. The study found that a menstrual flow length of 3-5 days was associated with a higher incidence of anemia (P=<0.001 chi-square 14.3). However, the number of sanitary pads used per day was not significant in relation to the prevalence of anemia (p=0.5 1.2). In conclusion, menstrual issues were found to be the leading cause of anemia among nursing students. Therefore, raising awareness about this health condition and implementing necessary measures can significantly enhance students' quality of life in educational institutions.